2022
DOI: 10.1037/dev0001440
|View full text |Cite
|
Sign up to set email alerts
|

Identity trajectories and narratives during the transition out of undergraduate education among Georgian emerging adults.

Abstract: The transition out of university education and into the workforce represents a turning point in terms of the evolution of one's goals, roles, responsibilities, relationships, and lifestyle. For this reason, this transition might create important challenges and opportunities for identity formation. The present mixed-method longitudinal study examined identity formation processes in a sample of Georgian final-year undergraduate students over an 11-month period at four different points before and after graduation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Conceptually, individuals who have become distressed and withdraw from engagement in identity commitments or exploration (i.e., ruminative exploration) could also be seen as possibly lacking in autobiographical reasoning (i.e., not seeing connections between past events and the current or future self). In line with the general concept of narrative processing driving stability and change within identity status, a recent study found participant narratives within each identity status did have some common themes that could illuminate the thought processes and life events that may contribute to identity formation (e.g., participants' familial, educational, and romantic experiences all seemed to influence their identity formation processes and subsequent identity status; Skhirtladze et al, 2022). Thus, we test whether the process of narration is a possible mechanism for changes in dual-cycle identity dimensions over time.…”
Section: Narrative Identity As a Mechanism Of Change In Exploration A...mentioning
confidence: 82%
“…Conceptually, individuals who have become distressed and withdraw from engagement in identity commitments or exploration (i.e., ruminative exploration) could also be seen as possibly lacking in autobiographical reasoning (i.e., not seeing connections between past events and the current or future self). In line with the general concept of narrative processing driving stability and change within identity status, a recent study found participant narratives within each identity status did have some common themes that could illuminate the thought processes and life events that may contribute to identity formation (e.g., participants' familial, educational, and romantic experiences all seemed to influence their identity formation processes and subsequent identity status; Skhirtladze et al, 2022). Thus, we test whether the process of narration is a possible mechanism for changes in dual-cycle identity dimensions over time.…”
Section: Narrative Identity As a Mechanism Of Change In Exploration A...mentioning
confidence: 82%
“…We highlight two integrative perspectives of specific relevance to the research reviewed herein. Process-oriented approaches need to be integrated with narrative approaches to capture not only identity processes at work but identity content as well through the lived experiences of individuals (Hihara et al, 2021;Skhirtladze et al, 2022;Syed, 2020).…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%